2022
DOI: 10.1364/oe.460151
|View full text |Cite
|
Sign up to set email alerts
|

Transparent dual-band ultraviolet photodetector based on graphene/p-GaN/AlGaN heterojunction

Abstract: Versatile applications have driven a desire for dual-band detection that enables seeing objects in multiple wavebands through a single photodetector. In this paper, a concept of using graphene/p-GaN Schottky heterojunction on top of a regular AlGaN-based p-i-n mesa photodiode is reported for achieving solar-/visible-blind dual-band (275 nm and 365 nm) ultraviolet photodetector with high performance. The highly transparent graphene in the front side and the polished sapphire substrate at the back side allows bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Although AlGaN has been widely used for DUV PDs based on their intrinsic bandgap tunability, most devices have focused on the 3D film type AlGaN. [26,[102][103][104] In 2021, Paramanik et al reported a DUV PD using an AlGaN/AlN QDs-in-wells structure, as illustrated in Figure 7g. [105] To selectively detect the DUV region, they constructed the MSM PDs which use horizontal carrier transport in AlGaN/AlN multiple quantum wells (MQW) (Figure 7h).…”
Section: Aluminum Gallium Nitride Quantum Dots (Algan Qds)-based Duv Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AlGaN has been widely used for DUV PDs based on their intrinsic bandgap tunability, most devices have focused on the 3D film type AlGaN. [26,[102][103][104] In 2021, Paramanik et al reported a DUV PD using an AlGaN/AlN QDs-in-wells structure, as illustrated in Figure 7g. [105] To selectively detect the DUV region, they constructed the MSM PDs which use horizontal carrier transport in AlGaN/AlN multiple quantum wells (MQW) (Figure 7h).…”
Section: Aluminum Gallium Nitride Quantum Dots (Algan Qds)-based Duv Pdmentioning
confidence: 99%
“…Although AlGaN has been widely used for DUV PDs based on their intrinsic bandgap tunability, most devices have focused on the 3D film type AlGaN. [ 26,102–104 ] In 2021, Paramanik et al. reported a DUV PD using an AlGaN/AlN QDs‐in‐wells structure, as illustrated in Figure 7g.…”
Section: Quantum Dot‐based Duv Pdsmentioning
confidence: 99%
“…III-nitride semiconductor materials possess remarkable characteristics of wide energy bandgap, high thermal conductivity, large electron mobility, robust radiation resistance, and excellent chemical stability [1][2][3]. III-nitride-based ultraviolet (UV) photodetectors (PDs) have the potential for achieving high responsivity, fast response, and low dark current 5 Authors of equal contribution. * Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…* Authors to whom any correspondence should be addressed. [4,5]. Moreover, the energy bandgap for (Al)GaN materials is adjustable that ranges from 3.4 eV to 6.2 eV covering 365 nm to 200 nm [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] The addition of a p-GaN layer to the AlGaN/GaN changes the resulting p-GaN/AlGaN/GaN HEMT (enhancement-mode) from normally-on to normally-off through band bending and suppression of 2-DEG at zero-bias, which leads to low dark current. [31][32][33][34][35] In previously reported enhancementmode p-GaN/AlGaN/GaN photodetectors, the p-GaN acted as the gate by the means of photo induced carriers. However, there are only a very few studies on the utilization of p-GaN/ AlGaN/GaN structure, and most of them focused on phototransistor mode of operation, where the area of the p-GaN optical gate is limited by the transistor geometry.…”
Section: Introductionmentioning
confidence: 99%